Magnetic reversibility accompanied by thermal hysteresis in magnetocaloric materials: A lock-in thermography study - Jorge Revuelta-Losada; Aun N. Khan; Luis M. Moreno-Ramírez; Jia Yan Law; Anit K. Giri; Victorino Franco (Materials & Design)
Lock-in infrared thermography (LIT) was used to obtain the reversible adiabatic temperature change (ΔTadrev) from an oscillating magnetic field up to a maximum of 1.5  T. Several paradigmatic magnetocaloric materials exhibiting diverse thermomagnetic phase transitions were studied: (1) Gd, undergoing a second-order transition; (2) LaFe11.38Mn0.28Si1.34-H undergoing a magneto-elastic first-order transition; and (3) Ni48.6Mn35.9In15.5 and (4) Ni36Co14Mn35Ti15 Heusler alloys, both undergoing magneto-structural first-order transition with varying degrees of overlap with the second-order transition of austenite and associated hysteresis. LIT increases ΔTadrev resolution by two orders of magnitude compared to traditional thermography. This advanced capability facilitates the detection of features in the responses that would otherwise be challenging to identify. Furthermore, the phase Φ with respect to the excitation serves as an indicator of the phase transition dynamics. Importantly, while the ΔTadrev measurements remain reversible against field oscillations, first-order thermomagnetic phase transitions driven by non-saturating fields show different behaviors for heating and cooling curves, manifesting thermal hysteresis and the irreversibility of the transition under those conditions. This highlights the significance of direct characterization methods of the magnetocaloric response over indirect approaches and its usefulness for the design of materials for efficient refrigeration devices.